2021
DOI: 10.3390/ijerph18041673
|View full text |Cite
|
Sign up to set email alerts
|

Definitions and Prevalence of Multimorbidity in Large Database Studies: A Scoping Review

Abstract: Background: Multimorbidity presents a key challenge to healthcare systems globally. However, heterogeneity in the definition of multimorbidity and design of epidemiological studies results in difficulty in comparing multimorbidity studies. This scoping review aimed to describe multimorbidity prevalence in studies using large datasets and report the differences in multimorbidity definition and study design. Methods: We conducted a systematic search of MEDLINE, EMBASE, and CINAHL databases to identify large epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 46 publications
1
34
0
1
Order By: Relevance
“…Our results showed that 36.8% of the inpatients living in Chengdu during the 2015-2019 time period had at least two chronic diseases, which is lower than that in the Netherlands (multimorbidity prevalence of 57%) [ 39 ], Spain (multimorbidity prevalence of 43.2%) [ 40 ], and Canada (multimorbidity prevalence of 53.3%) [ 6 ], but higher than that in the United Kingdom (multimorbidity prevalence of 19%) [ 14 ], Scotland (multimorbidity prevalence of 31.1%) [ 41 ], Singapore (multimorbidity prevalence of 26.2%) [ 42 ], Italy (multimorbidity prevalence of 15.3%) [ 43 ], and Denmark (multimorbidity prevalence of 21.6%) [ 44 ]. A scoping review found a wide range in multimorbidity prevalence in the general population as reported in studies using a large data set, from 15.3% to 68.4% [ 45 ]. The reported multimorbidity prevalence is still highly varied due to inconsistent measurements of chronic conditions and multimorbidity [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that 36.8% of the inpatients living in Chengdu during the 2015-2019 time period had at least two chronic diseases, which is lower than that in the Netherlands (multimorbidity prevalence of 57%) [ 39 ], Spain (multimorbidity prevalence of 43.2%) [ 40 ], and Canada (multimorbidity prevalence of 53.3%) [ 6 ], but higher than that in the United Kingdom (multimorbidity prevalence of 19%) [ 14 ], Scotland (multimorbidity prevalence of 31.1%) [ 41 ], Singapore (multimorbidity prevalence of 26.2%) [ 42 ], Italy (multimorbidity prevalence of 15.3%) [ 43 ], and Denmark (multimorbidity prevalence of 21.6%) [ 44 ]. A scoping review found a wide range in multimorbidity prevalence in the general population as reported in studies using a large data set, from 15.3% to 68.4% [ 45 ]. The reported multimorbidity prevalence is still highly varied due to inconsistent measurements of chronic conditions and multimorbidity [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A scoping review found a wide range in multimorbidity prevalence in the general population as reported in studies using a large data set, from 15.3% to 68.4% [ 45 ]. The reported multimorbidity prevalence is still highly varied due to inconsistent measurements of chronic conditions and multimorbidity [ 45 , 46 ]. Additionally, a study using claims data in Beijing reported that the prevalence of multimorbidity was 51.6% and 81.3% for middle-aged adults (45-59 years) and older adults (≥60 years), respectively [ 47 ], which were higher than the respective prevalences of 41.7% and 75.2% in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Because there is no uniform gold standard for measuring multimorbidity, prevalence depends on the number of chronic diseases studied or the population studied. From 2012 to 2019, the prevalence of chronic multimorbidity in the current population ranged from 15.3 to 93.1% [ 6 ]. However, it has long been noted that for older patients treated in ambulatory care settings, the criteria of three chronic diseases are considered more valid cut-off points for multimorbidity than the usual criteria of two chronic diseases [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the meta-analysis of multimorbidities, the chronic diseases included in the 20 literatures were classified and counted, among which the 11 diseases with the most inclusion were included in our study. Therefore, the conclusions of our study are considered reliable [ 22 ]. Jiayi Gu et al [ 23 ] in a survey of the prevalence of multimorbidity among the elderly in Chinese urban areas, found that the prevalence rate was 49.4%, which was similar to the results of this study.…”
Section: Discussionmentioning
confidence: 89%